Summary of a workshop on U.S. natural gas demand, supply, and technology : looking toward the future (National Academies Press, 2003)
The workshop examined the following three questions: (1) What projections have been made by government agencies for the U.S. supply of and demand for natural gas over the next 10 to 20 years? (2) Where are the current natural gas reserves and resources? (3) By what means and by how much can future reserves, resources, and production be increased?